FIRST RECORD OF MEGASCOLECID EARTHWORMS FROM SELECTED REGION OF THE GANGETIC PLAIN OF BIHAR, INDIA - ROHIT SRIVASTAVA; MRIDULA KUMARI; DEOKANT; SAMIR KUMAR MANDAL; SWETA SUBARNA; NEHA SWATI BAXLA; SHALINI 1 , SHEELU KACHHAP; MANOJ KUMAR; SUKUMAR DANDAPAT; RAKESH RANJAN; MANORANJAN PRASAD SINHA (The Bioscan, 2022)
The family Megascolecidae, which is the most speciose family of earthworms, has been found to be represented by five species belonging to three genera Lampito Kinberg, Metaphire Sims and Easton and Perionyx Perrier and the species are Lampito mauritii Kinberg, Metaphire planata Gates, Metaphire posthuma Vaillant, Perionyx sansibaricus Michaelsen, Perionyx millardi Stephenson, which is the first report from the Gangetic plain of Bihar. Out of these five, three species, Lampito mauritii, Perionyx sansibaricus and Perionyx millardi are native and rest two are peregrine. Three species out of the five namely Lampito mauritii, Metaphire planata and Metaphire posthuma are endogeic and Perionyx sansibaricus and Perionyx millardi are epigeic from ecological category view point. The occurrence of these species has been discussed in particular reference to habitat characteristics.